2022
DOI: 10.1039/d2lc00150k
|View full text |Cite
|
Sign up to set email alerts
|

Rheotaxis quality index: a new parameter that reveals male mammalian in vivo fertility and low sperm DNA fragmentation

Abstract: The female reproductive tract simultaneously guides and selects high-quality sperm using rheotaxis in mammalian species. Sperm quality, however, is traditionally evaluated only by their movement velocities and concentration using computer-assisted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…To quantify the sperm accumulation in the strictures, we have used the algorithm we developed for RHEOLEX. 41 This algorithm calculates the changes in pixel intensity for consecutive frames and obtains the average intensity for 200 images to generate signal contours (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To quantify the sperm accumulation in the strictures, we have used the algorithm we developed for RHEOLEX. 41 This algorithm calculates the changes in pixel intensity for consecutive frames and obtains the average intensity for 200 images to generate signal contours (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Previously we developed a method of characterizing mammalian sperm rheotaxis and concluded that spermatozoa from bulls with higher fertilization rates show higher rheotaxis ability. 41 Here, we postulated that sorting spermatozoa with higher rheotaxis capability could result in better fertilization outcomes in IVF cycles. To test this, we designed and characterized a high throughput microfluidic platform to separate spermatozoa with various rheotaxis abilities within a network of parallel strictures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human sperm from samples showing greater positive rheotaxis were demonstrated to have more normal morphology and better genomic quality ( De Martin et al, 2017 ; Ataei et al, 2021 ; Sharma et al, 2022 ). Recently, it was reported that rheotaxis success of bull sperm was positively correlated with bull fertility ( Yaghoobi et al, 2022 ). Similarly, it has been observed that the selection of rheotactic Mus musculus mouse sperm in vitro increased fertilization success and quality of early embryonic development ( Romero-Aguirregomezcorta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Motilitas spermatozoa merupakan parameter yang sangat penting untuk mengevaluasi tingkat fertilitas spermatozoa (Yaghoobi et al, 2022). Nilai rata-rata persentase motilitas berdasarkan hasil uji Duncan (α=0,05) menunjukkan adanya perbedaan nyata pada setiap perlakuan (Tabel 1)…”
Section: Motilitas Spermatozoaunclassified